Artificial neural network based color identification and detection to help color blind people. - Budisusila, Eka Nuryanto; Hapsari, Jenny Putri; Ismail, Munaf (Technology & Disability, 2026)
Background: Color vision defects (CVD), another name for color blindness, is a condition characterized by signs of failure of the optic nerve, which connects to the brain. People who suffer from color blindness have trouble identifying colors both physically and perceptually. Thus, that those who suffer from it are unable to appropriately differentiate between colors. Objective: In order to recognize colors, victims require a tool. A technology that can assist color blind people in recognizing colors is being tried in this investigation. Methods: The Artificial Neural Network (ANN) algorithm is embedded into the hardware of the system, which is based on artificial intelligence (AI). A light sensor based on the Red, Green, and Blue (RGB) filter is employed. RGB data will be sent into the ANN. An Arduino Due microcontroller is equipped with an ANN program that functions as a data processor. This system's outputs are the color speech on the speaker and the color text on a dot-matrix LED display. Results: This system's output is represented by the color that is shown on the LED dot-matrix display board. The method is successful in identifying all 16 of the training colors. Targets and outputs have an MSE of roughly 0.0001. Conclusions: The findings of this study should assist those who are color blind in identifying colors by listening to the speaker's sound and reading the display board that the system displays.